2017
DOI: 10.1089/omi.2017.0112
|View full text |Cite
|
Sign up to set email alerts
|

“Omics” of Food-Borne Gastroenteritis: Global Proteomic and Mutagenic Analysis ofSalmonella entericaSerovar Enteritidis

Abstract: Salmonella Enteritidis causes food-borne gastroenteritis by the two type three secretion systems (TTSS). TTSS-1 mediates invasion through intestinal lining, and TTSS-2 facilitates phagocytic survival. The pathogens' ability to infect effectively under TTSS-1-deficient background in host's phagocytes is poorly understood. Therefore, pathobiological understanding of TTSS-1-defective nontyphoidal Salmonellosis is highly important. We performed a comparative global proteomic analysis of the isogenic TTSS-1 mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This notion is consistent with our in-vitro data showing that while STM is able to utilize ethanolamine and citrate as a sole carbon source, SPA cannot grow or grows much slower on these sources. Previous studies have shown that deficiency for citrate lyase activity (citF) leads to significant reduction in STM survival inside macrophages [77] and that an STM mutant that cannot utilize citrate is highly attenuated in the mouse [78]. Similarly, ethanolamine is released by host tissues during inflammation and a study by Thiennimitr and colleagues in mice has shown that ethanolamine metabolism provides a growth advantage to STM during intestinal colonization [75].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This notion is consistent with our in-vitro data showing that while STM is able to utilize ethanolamine and citrate as a sole carbon source, SPA cannot grow or grows much slower on these sources. Previous studies have shown that deficiency for citrate lyase activity (citF) leads to significant reduction in STM survival inside macrophages [77] and that an STM mutant that cannot utilize citrate is highly attenuated in the mouse [78]. Similarly, ethanolamine is released by host tissues during inflammation and a study by Thiennimitr and colleagues in mice has shown that ethanolamine metabolism provides a growth advantage to STM during intestinal colonization [75].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This notion is consistent with our in-vitro data showing that while STM is able to utilize ethanolamine and citrate as a sole carbon source, SPA cannot grow or grows much slower on these sources. Previous studies have shown that deficiency for citrate lyase activity (citF) leads to significant reduction in STM survival inside macrophages (72) and that an STM mutant that cannot utilize citrate is highly attenuated in the mouse (73). Similarly, ethanolamine is released by host tissues during inflammation and a study by Thiennimitr and colleagues in mice has shown that ethanolamine metabolism provides a growth advantage to STM during intestinal colonization (70).…”
Section: Discussionmentioning
confidence: 99%
“…This platform has been growing steadily and widely utilized with the supplementation of advances in both mass spectrometry and bioinformatics [ 155 ]. In detection of Salmonella Enteritidis, proteomic approaches have been used to detect isogenic Type Three Secretion System-I (TTSS-I) known as M1511 and its wild-type isolate, P125109 using a high-resolution Fourier transform mass spectrometer [ 156 ]. For Escherichia coli identification, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-ToF MS) can also be used because it is a rapid, low cost, reliable and accurate proteomic method for E. coli identification up to the subspecies level compared with classical culture microbiological techniques [ 157 , 158 ].…”
Section: Omics-based Technologies For Age Diagnosis and Managementmentioning
confidence: 99%